The Prevalence of Diurnal Urinary Incontinence and Enuresis and Quality of Life: Sample of School - Savaser, Sevim; Kizilkaya Beji, Nezihe; Aslan, Ergul; Gozen, Duygu (Urology Journal, 2018)
Purpose: Enuresis can cause loss of self-esteem in children, change relations with family and friends, and decrease the school success. This study was conducted to determine the prevalence of urinary incontinence (UI) in school children aged between 11-14 years and identify the emotions and social problems of enuretic children. Materials and Methods: A mixed methods approach was used on a group of students who reported UI by combining quantitative data from school population-based cross-sectional design with qualitative data using in-depth interview techniques. The data of this descriptive and cross-sectional study were collected from 2750 primary school students aged between 11-14 years in Istanbul. Results: The overall prevalence of UI was 8.6% and decreased with age. Prevalence of the diurnal enuresis in children was 67.9% and all of them had non-monosymptomatic enuresis. 83.3% of the children were identified with secondary enuresis for 1-3 years. UI was significantly more common in boys and those who had frequent urinary infections, whose first degree relatives had urinary incontinence problem in childhood, and who reported low socioeconomic level in the family. The emotional and social effects of urinary incontinence were given in the context of children's own expressions. Conclusion: Urinary incontinence is an important problem of school-age children. In this study the prevalence of UI was found to be 8.6%, diurnal UI and secondary enuresis were very common, and all of the children were non-monosymptomatic. Enuresis has negative emotional and social effects on children.